Pojęcie bezpieczeństwa w obowiązującym systemie prawa — kilka refleksji na temat normatywizacji problematyki bezpieczeństwa - Lisowski, Piotr (Wydawnictwo Uniwersytetu Wrocławskiego, 2016)
The paper demonstrates that the notion of security is a lawyers’ and not legal concept, and explains why it is so. It also introduces the basic classifications of security understood from both legal and lawyers’ perspectives. In addition to that, the key determinants in the process of normative regulation of security are identified. The paper concludes with the analysis of basic difficulties and threats which can occur when the issue of security is being incorporated into the legal order.
Keywords: security; legal system; normativisation of security issues